2018
DOI: 10.1111/ajag.12493
|View full text |Cite
|
Sign up to set email alerts
|

Workplace design for the Australian residential aged care workforce

Abstract: Key workplace design features that matter to RAC staff in a 'shared workspace' exist. Increasing demands upon RAC requires evidence-based workplace design policy and evaluation approaches that support RAC staff to work in RAC shared workspaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…They identify ten influential factors (e.g., thermal comfort, air quality, lighting, noise, user control, privacy, concentration, communication, social contact, and spatial comfort), divided into physical comfort, functional, and psychological comfort. Moreover, Naccarella et al (2018) state that employees want to work in a user-controllable, comfortable, and hygienic workplace where they can ‗feel at home.' Septiari (2020) studies the correlation between the physical work environment and the level of fatigue on packaging productivity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They identify ten influential factors (e.g., thermal comfort, air quality, lighting, noise, user control, privacy, concentration, communication, social contact, and spatial comfort), divided into physical comfort, functional, and psychological comfort. Moreover, Naccarella et al (2018) state that employees want to work in a user-controllable, comfortable, and hygienic workplace where they can ‗feel at home.' Septiari (2020) studies the correlation between the physical work environment and the level of fatigue on packaging productivity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…From the employee’s perspective, the interesting issues of office renovation are well-being and a healthy work environment (Leather et al , 2003). Employees want to work in a hygienic, comfortable and user controllable workplace where they can feel at home (Naccarella et al , 2018). Another study about the user value of office buildings distinguished the meaning of well-being into psychological well-being and physical well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study on the physical environment [29] identified workplace design features that influence whether residential aged care staff feel valued, productive, safe, belonging and connected. Key design features were: a home-like environment; access to outdoor spaces; a high-quality indoor environment; and access to safe, open, comfortable workplaces.…”
Section: Theme 2: Environmental Influencesmentioning
confidence: 99%